2016
DOI: 10.1002/asia.201600538
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Charge‐Transfer State of 4‐Carbazolyl‐3‐(trifluoromethyl)benzoic Acid: Photophysical Property and Application to Reduction of Carbon−Halogen Bonds as a Sensitizer

Abstract: The photoinduced persistent intramolecular charge-transfer state of 4-carbazolyl-3-(trifluoromethyl)benzoic acid was confirmed. It showed a higher catalytic activity in terms of yield and selectivity in the photochemical reduction of alkyl halides compared to the parent carbazole. Even unactivated primary alkyl bromides could be reduced by this photocatalyst. The high catalytic activity is rationalized by considering the slower backward single-electron transfer owing to the spatial separation of the donor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“… a) Working hypothesis of phototriggered nitrile formation. b) Inspiring findings reported in our previous study …”
Section: Figuresupporting
confidence: 68%
See 1 more Smart Citation
“… a) Working hypothesis of phototriggered nitrile formation. b) Inspiring findings reported in our previous study …”
Section: Figuresupporting
confidence: 68%
“…The thus‐formed iminyl cation would then undergo a deprotonation, leading to the nitrile group. Previously, we have observed a fast BET from the carbon radical to the radical cation of carbazole derivative 1 (Scheme b) . Considering these previous findings, we expected that, in analogy to the carbon radical, the iminyl radical would undergo a BET with a suitable carbazole‐based photosensitizer rapidly enough to compete with the other radical reactions involved with the iminyl radical.…”
Section: Figurementioning
confidence: 82%
“…Previously, we reported that a 3,6-dimethoxycarbazole derivative (CAR3, Scheme 1), which has an electron-deficient aryl substituent on the carbazole nitrogen, could catalyze the photochemical dehalogenation of unactivated primary alkyl bromides. 10 The fact that carbazole CAR3 showed higher reducing ability than CAR2 (Scheme 1) was rationalized by assuming that the charge-transfer (CT) excited state of CAR3 effectively suppresses back electron transfer. However, the CAR3 could not reduce some of the more demanding substrates, such as aryl bromides and organochlorides.…”
Section: Resultsmentioning
confidence: 99%
“…(3) The ideal PC should absorb photons at wavelengths longer than 350 nm to avoid unwanted direct excitation of substrates and allow the utilization of the UVA and visible-light region of sunlight. (4) Based on our previous finding, 10 the CT excited state helps to retard the unproductive back electron transfer. 12 DFT calculations for the parent molecule (carbazole) showed large orbital coefficients at C3 and C6 in the HOMO, while nodes exist on these two carbons in the lowest unoccupied molecular orbital (LUMO) (Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our laboratory has been focusing on the development of nonmetal PCs with high reducing ability . We observed that the carbazole-based visible-light-activated PC PC1 , bearing excited-state oxidation potentials as negative as −2.75 V versus SCE, exhibited high catalytic performance, enabling the reduction of unactivated chloroarenes ( E red [PhCl/PhCl •– ] = −2.88 V vs SCE) and even a fluoroarene via the SET mechanism. The installation of dimethylamino groups at the carbazole 3- and 6-positions provided two advantages: (1) A 40 nm bathochromic shift over that of PC2 in the absorption spectrum, enabling visible-light activation and (2) increased excited-state reducing ability [ E ox * = −2.75 V ( PC1 ) versus −2.47 V ( PC2 )].…”
Section: Introductionmentioning
confidence: 99%